Modeling specialty store customers' buy/no-buy decisions. Issue 12 (23rd November 2017) - Goudge, Darrell; Good, Megan C.; Hyman, Michael R.; Aguirre, Grant
Abstract : Purpose: The purpose of this paper is to develop, test, and validate a model in a specialty retail environment to assess the influence of a salesperson's sales- or customer-orientation and customer characteristics related to buy/no-buy decisions. Design/methodology/approach: Backward stepwise discriminant analysis was used to identify variables that most differentiated buyers from non-buyers. The discriminant model was estimated with survey data provided by a judgment sample of consumers asked to recall details about a recent in-store purchase experience ( n =240). One significant discriminant function emerged. The model correctly classified 87.5 percent of buy/no-buy decisions by consumers in a separate validation sample ( n =40). Findings: Customers who believe a salesperson is sales oriented (i.e. only interested in closing) are more likely to make a no-buy decision even when retailer-related attributes – such as positive prior experience with the retailer, susceptibility to normative interpersonal influence, and positive attitude toward retailing – suggest otherwise. Surprisingly, neither customer orientation nor susceptibility to interpersonal informational influence relates significantly to making a buy/no-buy decision. Practical implications: Specialty retailers should avoid a sales-outcome-based orientation. To add value in a competitive marketplace where buyers can avoid salespeople, the focus of a sales interaction should be on identifying customer needs and characteristics. Originality/value: Adaptations of sales people's personas and selling efforts – fostered by new managerial training practices – and the need for specialty retailers to adopt behavior-based control systems are suggested. In addition, sales or customer orientation typically is reported by the salesperson. Here, customers' belief – which is more germane to modeling buy/no-buy decisions – designates the salesperson's orientation.